Teaching Strategies that Inspire: Examining the Impact of Instructional Methods on Students’ Motivation and Mathematics Achievement - Dahal, Prem Prasad (Cognition, 2026)
Mathematics is a fundamental subject that supports logical reasoning, problem-solving, and it provides analytical skills which is essential for all students in academic and professional development. The main objectives of this study were to identify the perceptions of students about the impact of instructional methods on students’ motivation and mathematics achievement in Nepal and to determine the relationship between instructional methods, students’ motivation and mathematics achievement. Expected value theory and Self-determination theories were taken as the theoretical base. In this study, only a quantitative approach was used, and 196 students were used as a sample, which was selected using a stratified random sampling method. Likert 5-point scale questionnaire was used to examine the perceptions of students in different headings, and the validity of items was tested by the expert judgement method, and the reliability was tested using Cronbach’s alpha value. The findings show that the students had positive perceptions about all three variables: instructional methods, motivation in mathematics, and mathematics achievement. Also, there was a strong positive correlation between the variables which shows that effective and engaging teaching methods increase a higher level of motivation of students in learning mathematics, and to achieve good achievement in mathematics. Therefore, the teacher must prioritize different teaching methods which helps students in psychological engagement and academic success in mathematics.